2020
DOI: 10.1007/s00216-020-03093-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeated double cross-validation applied to the PCA-LDA classification of SERS spectra: a case study with serum samples from hepatocellular carcinoma patients

Abstract: Intense label-free surface-enhanced Raman scattering (SERS) spectra of serum samples were rapidly obtained on Ag plasmonic paper substrates upon 785 nm excitation. Spectra from the hepatocellular carcinoma (HCC) patients showed consistent differences with respect to those of the control group. In particular, uric acid was found to be relatively more abundant in patients, while hypoxanthine, ergothioneine, and glutathione were found as relatively more abundant in the control group. A repeated double cross-valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
(60 reference statements)
0
25
0
2
Order By: Relevance
“…A possible explanation can reside in the origin of the serum used in our study. The variation in relative intensity in HX and ERG bands has been linked to the spectral variability due to different clinical states of patients [ 33 , 34 , 35 ]. With respect to that, a standard commercial serum can easily present a lower HX and ERG concentration since no metabolite standardization or quantification is available for commercial serum.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation can reside in the origin of the serum used in our study. The variation in relative intensity in HX and ERG bands has been linked to the spectral variability due to different clinical states of patients [ 33 , 34 , 35 ]. With respect to that, a standard commercial serum can easily present a lower HX and ERG concentration since no metabolite standardization or quantification is available for commercial serum.…”
Section: Resultsmentioning
confidence: 99%
“…Example of how characteristic ET bands (highlighted with grey areas) are observed in LF‐SERS spectra of a variety of human biofluids of healthy donors. SERS spectrum of (a) ET [19] is compared to SERS spectra of (b) erythrocytes lysate [19], (c) serum [29], (d) gingival crevicular fluid [28], (e) seminal plasma [50] and (f) cerebrospinal fluid [32]. All spectra were obtained with an excitation at 785 nm, and using Ag nanoparticles as substrates, with the exception of (f), for which Au nanoparticles were used.…”
Section: Et In Lf‐sers Of Biofluidsmentioning
confidence: 99%
“…For instance, preliminary studies have suggested that LF‐SERS spectroscopy on serum/plasma samples can be used to distinguish patients with several types of hepatocellular carcinoma (HCC) from patients with chronic hepatitis B (CHB), normal individuals, or patients with oesophageal carcinoma (EC) [8,29,33,45]. Recent serum data published by Gurian et al.…”
Section: Relevance Of Et In Diagnostic Studies Using Blood Serum and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The rdCV approach [35][36][37] estimates the optimum model complexity (given by the number of PLS components, AOPT) separately from estimating the prediction performance for new objects. [38] Furthermore, the variability of the performance criteria is characterized by repeated random splits into calibration and test sets. The essential parameters used for rdCV are as follows: the numbers of segments in outer and inner loop are 3 and 7, respectively; the number of repetitions is 50, resulting in 50 test-set predictions ŷ for each object, and 150 estimations of the optimum number of PLS components, with the most frequent value taken as the final AOPT.…”
Section: Application In Qspr Modelsmentioning
confidence: 99%